2023
DOI: 10.3390/jrfm16010035
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxes and Tensions in Interorganizational Relationships: A Systematic Literature Review

Abstract: This paper examines the literature on paradoxes and tensions in interorganizational relationships (IORs) and identifies how such tensions are managed in interorganizational settings. In a systematic literature review, we analyzed 95 papers published between 1997 and 2021 on the subject of paradoxes in IORs. The sample showed a variety of paradoxes occurring in different interorganizational contexts, such as knowledge sharing and protection, short- and long-term orientation, and exploration and exploitation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 112 publications
(157 reference statements)
0
3
0
Order By: Relevance
“…However, though this relationship is weak, this can also imply that while strategy is meaningful to SMEs it is not quite vital. As brought out above, the implementation of a strategy comes along with some amount of rigidity thereby limiting the amount or range of changes that can be made by the business (Lloyd-Kuzik et al, 2023; Marcos Vinícius, et al, 2023). It has been reported that one of the principal strengths of SMEs is flexibility and the ability to make rapid changes due to shortened decision-making processes (Benzidia, & Makaoui, 2020; Levy & Powell, 1998;Trzcieliński, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, though this relationship is weak, this can also imply that while strategy is meaningful to SMEs it is not quite vital. As brought out above, the implementation of a strategy comes along with some amount of rigidity thereby limiting the amount or range of changes that can be made by the business (Lloyd-Kuzik et al, 2023; Marcos Vinícius, et al, 2023). It has been reported that one of the principal strengths of SMEs is flexibility and the ability to make rapid changes due to shortened decision-making processes (Benzidia, & Makaoui, 2020; Levy & Powell, 1998;Trzcieliński, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This method is recommended when the phenomenon under study is a contemporary issue and the researchers have the opportunity to access contextual data with the intention of exploring how and why changes happened (Yin 2009). The case study method is also prevalent in existing literature examining governance tensions within interorganizational networks (Fortes et al 2023). Thus, the unit of analysis in our study is at the network level.…”
Section: Methodsmentioning
confidence: 99%
“…The concept of tension within the literature on interorganizational networks is multifaceted. Tensions are sometimes interpreted as paradoxes, as negative consequences arising from these paradoxes, or as conflicting relationships between two or more elements (Fortes et al 2023). Traditionally viewed through a negative lens, these tensions can also strengthen partnerships, enhance resource sharing, build trust, and improve regulatory frameworks when addressed creatively (Lee 2022).…”
Section: Tensions In the Governance Of Interorganizational Networkmentioning
confidence: 99%
See 1 more Smart Citation